Highly permeable and fouling-resistant hollow fiber membranes for reverse osmosis. (2nd November 2019) - Zhang, Yu; Yang, Liming; Pramoda, Kumari Pallathadka; Gai, Wenxiao; Zhang, Sui
Graphical abstract: Highlights: A green synthesis approach for anti-fouling modifications. Molecular drilling effect by zwitterionic copolymers enhances water permeability. Pure water permeability 10.5 ± 0.5 L m −2 h −1 bar −1, NaCl rejection of 98.1 ± 0.2%. Fouling resistant to various foulants and realistic feed. Abstract: This paper reports a fast, cost-effective and environmental-friendly method to engineer the membrane structure, and simultaneously enhance the permeance and fouling resistance in reverse osmosis (RO). By free radical polymerization in water, copolymers containing fouling-resistant zwitterionic and hydroxyl-based anchoring groups are synthesized and quickly bonded to the polyamide membrane surface. The copolymer also functions as the molecular engine to reduce the thickness of the polyamide layer and drill nanopores, thereby re-shaping its 3D structure for higher permeability. It is revealed that by design of the size and functionality of the copolymer, the water permeability and salt rejection may be simultaneously increased. Our membrane demonstrates a pure water permeability of 10.5 L m −2 h −1 bar −1, NaCl rejection of 98.1%, and superior fouling resistance towards various foulants and realistic feed. This paper provides a new perspective for the development of highly permeable, fouling-resistance membranes not only for RO, but also nanofiltration.